Prediction of Land Use Change and Carbon Storage in Lijiang River Basin Based on InVEST-PLUS Model and SSP-RCP Scenario - Jing Jing; Feili Wei; Hong Jiang; Zhantu Chen; Shuang Lv; Tengfang Li; Weiwei Li; Yi Tang (Land)
Global climate change and changes in land use structures during rapid urbanization have profoundly impacted ecosystem carbon storage. Previous studies have not combined different climate scenarios and land use patterns to predict carbon storage. Using scenarios from both the InVEST-PLUS model and SSP-RCP, combined with multi-source remote sensing data, this study takes the Lijiang River Basin as the study area to explore the dynamic changes in land use and carbon storage under different climate scenarios. The findings are as follows: (1) From 2000 to 2020, cultivated and construction land increased, while forest land significantly decreased, lowering from 4331.404 km2 to 4111.936 km2. This land use change mainly manifests in the significant transformation of forest land into cultivated and construction lands. Under different climate scenarios, the cultivated and construction lands will continue to expand, the forest land will decrease, and the grassland area will increase. (2) Total carbon storage decreased significantly from 2000 to 2020, with forest carbon storage changing the most significantly, for a total reduction of 5,540,612.13 tons, followed by grassland and water area. Regardless of the future scenario, the total carbon storage in the Lijiang River Basin will experience a decreasing trend; the decline in carbon reserves is most significant in the SSP585 scenario and smallest in the SSP126 scenario, with slight increases even appearing in some regions. (3) From the perspective of land use change, the large-scale expansion of construction land in the process of rapid urbanization has occupied a large amount of ecological land, such as forests and grasslands, and this is the main reason for the reduction in total carbon storage in the basin. From the perspective of climate change scenarios, a global temperature increase caused by a high-emission scenario (SSP585) may exceed the optimal growth temperature for some plants, inhibit the carbon absorption capacity of vegetation, and thus reduce the carbon fixation capacity of forest land and grassland. Therefore, to maintain long-term climate goals and sustainable development, the SSP126 scenario should be prioritized to strengthen the protection of forest resources in the northern and central regions of the Lijiang River Basin, balance the relationship between ecological protection and urbanization, avoid the occupation of ecological land by excessive urbanization, and improve the carbon sink potential of the basin. These research results can provide a scientific basis for the optimization of land spatial patterns, ecological restoration and protection, and the enhancement of carbon sink potential in the Lijiang River Basin under the “double carbon” goal.